2018
DOI: 10.1097/ico.0000000000001732
|View full text |Cite
|
Sign up to set email alerts
|

Current Practice Patterns and Opinions on the Management of Recent-Onset or Chronic Herpes Zoster Ophthalmicus of Zoster Eye Disease Study Investigators

Abstract: Approximately half of ZEDS investigators treat HZO with prolonged oral antivirals, in addition to topical steroids, and two-thirds believe that it is effective. Completion of ZEDS is feasible and necessary to determine whether or not these practices are effective. Participation in this study is necessary to obtain evidence to support treatment that many ophthalmologists use and believe is effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The treatment of HZK centres on oral and/or topical antivirals for active epithelial disease and topical steroids for immunemediated stromal and endothelial disease. [22][23][24]27 HZK is often recurrent or chronic, sometimes complicated by NK, and can ultimately lead to stromal scarring or endothelial dysfunction, possibly requiring surgery. 8 Vaccination is an effective method of decreasing the incidence of HZO.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment of HZK centres on oral and/or topical antivirals for active epithelial disease and topical steroids for immunemediated stromal and endothelial disease. [22][23][24]27 HZK is often recurrent or chronic, sometimes complicated by NK, and can ultimately lead to stromal scarring or endothelial dysfunction, possibly requiring surgery. 8 Vaccination is an effective method of decreasing the incidence of HZO.…”
Section: Discussionmentioning
confidence: 99%
“…8 In a survey from 2012, 27 56% of corneal specialists reported that they believed oral antiviral prophylaxis was effective, and that number increased to 71% in a 2019 survey. 22 In a retrospective study by Miserocchi and colleagues, 35% of eyes affected by HZO and 39% of eyes affected by HSV had fewer episodes of inflammation with use of low-dose antiviral prophylaxis. 35 As this decrease in HSV recurrence was similar to that found in the Herpetic Eye Disease Study, 36 it is possible that low-dose, suppressive antiviral therapy could also work for HZ.…”
Section: Chronic and Recurrent Herpes Zoster Keratitismentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys of ZEDS study investigators at the start of enrollment in 2017 and 2 years later showed that an increasing percentage of investigators believe that suppressive antiviral treatment is effective in HZO and that this is contributing to enrollment below expectations. 13,14 Challenges with enrollment below expectations led to expansion of participating clinical centers (PCCs) to Canada and New Zealand, as well as modifications in statistical power and study population calculations (see PCC selection and Statistical considerations sections).…”
Section: Trial Overview and Aimsmentioning
confidence: 99%
“…Currently, many clinicians use prolonged oral antivirals in this patient population; studies, such as the Zoster Eye Disease Study (ZEDS), are currently being undertaken to determine optimal practice. 16 Finally, a comprehensive review of a patient's complete history of systemic pathologies and initiation of appropriate topical antimycotic therapy are of paramount importance to help decrease the need for surgical intervention and optimize the potential for visual rehabilitation in this challenging patient population. In our patient's situation, despite advanced PLK at the time of presentation, she responded favorably well to topical voriconazole and did not require any surgical intervention.…”
Section: Dovepressmentioning
confidence: 99%